Critical period for better nutrition among severely acute malnourished children up to two years of age: a hospital-based case-control study, Gujarat, Western India - Solanki, Harsha M.; Gosalia, Vibha V.; Bhitora, Rujal D. (International Journal Of Community Medicine And Public Health, 2023)
Background: Nutrition in the first two years of life is important for growth and development among children. To tackle undernutrition during this period, timely initiation of breastfeeding and quality of complementary feeding practices are essential. So, this study was planned to determine feeding practices associated with severe acute malnutrition children. Methods: This was hospital-based case-control study with 1:1 ratio of cases (77) and controls (77). Cases and controls were matched for age and sex. Cases were selected from Nutritional Rehabilitation Centre and controls from Immunization clinic. Mothers were interviewed about feeding practices, immunization status and illness of their child. Weight and height of children were also measured. Results: Children who received pre-lacteal feeding were associated with SAM. Most of cases (62.3%) and controls (70.1%) had received breastfeeding within 1 hour of birth. Among children of <7 months age, 71.4% cases breast-fed <8 times in 24 hours. Among children of 7 months to 2 years, SAM was associated with children who were not received complementary feeding (CF) at correct age, not received semi-solid/solid diet, CF not added with ghee/oil and feeding frequency <5 times in day. Among cases 18.2% and only 1.3% controls had >3 ARI episodes in last 6 months. Conclusions: Among identified independent risk factors (p<0.05), type of CF, not adding ghee/oil in CF and feeding frequency (BF+CF) <5 times were associated with SAM among 7 months to 2 years. Hospitalization history and >3 ARI episodes in last 6 months were also associated with SAM.